Influence of lower limb configuration on walking cost in Late Pleistocene humans - Hora, Martin; Sladek, Vladimir (Journal of human evolution, 2014)
It has been proposed that Neandertals had about 30% higher gross cost of transport than anatomically modern humans (AMH) and that such difference implies higher daily energy demands and reduced foraging ranges in Neandertals. Thus, reduced walking economy could be among the factors contributing to the Neandertals' loss in competition with their anatomically modern successors. Previously, Neandertal walking cost had been estimated from just two parameters and based upon a pooled-sex sample. In the present study, we estimate sex-specific walking cost of Neandertals using a model accounting for body mass, lower limb length, lower limb proportions, and other features of lower limb configuration. Our results suggest that Neandertals needed more energy to walk a given distance than did AMH but the difference was less than half of that previously estimated in males and even far less pronounced in females. In contrast, comparison of the estimated walking cost adjusted to body mass indicates that Neandertals spent less energy per kilogram of body mass than AMH thanks to their lower limb configuration, males having 1-5% lower and females 1-3% lower mass-specific net cost of transport than AMH of the same sex. The primary cause of high cost of transport in Neandertal males is thus their great body mass, possibly a consequence of adaptation to cold, which was not fully offset by their cost-moderating lower limb configuration. The estimated differences in absolute energy spent for locomotion between Neandertal and AMH males would account for about 1% of previously estimated daily energy expenditure of Neandertal or AMH males.
Keywords: Neanderthals; zkameněliny; mladiství; Middle Aged; mužské pohlaví; Adult; mladý dospělý; Fossils; neandertálci; Walking; kosti stehna a bérce; Lower Extremity; Lower limb length; Young Adult; antropologie fyzická; ženské pohlaví; Locomotion; chůze; zvířata; Humans; Posture; Anthropology, Physical; lidé středního věku; Neandertal; Anatomically modern humans; Relative tibial length; dospělí; dolní končetina; Female; Leg Bones; Adolescent; lidé; Male; Animals